POTENTIAL PEGAGAN LEAVES (CENTELLA ASIATICA (L.)) AS BURN HEALER AND ANTIBACTERIAL AGAINST STAPHYLOCOCCUS AUREUS - Ulupalu, Fadila Fauzia Mutmaina; Azizah, Rizqi Nur; Sukmawati, Sukmawati (Fakultas Farmasi, Universitas Muslim Indonesia, 2022)
Pegagan leaves (Centella asiatica (L.)) in the know contain flavonoids, saponins tannin and asiaticosides which have the effect of wound healing and antibacterial. This research aims to review scientific articles related to the potential of pegagan leaves in healing burns and as an antibacterial against Staphylococcus aureus. In this study using the literature study method where articles were obtained from the Google Scholar database, then obtained 10 articles that fit the inclusion and exclusion criteria. The review results show that pegagan leaves have activity in healing burn and antibacterial activity against Staphylococcus aureus because they contain asiatic acid, saponins, flavonoids and tannins. The conclusion of this study is that pegagan leaves have the potential as wound healing of burns with an effective extract concentration of ethanol extract concentration of 25 % and ethyl acetate extract 0.33 % and pegagan leaves potentially as antibacterial to Staphylococcus aureus with effective extract concentrations, viz ethanol extract concentrations of 100 % and ethyl acetate extracts of concentrations of 70 %.